A novel biomass gasification micro-cogeneration plant: Experimental and numerical analysis. (1st September 2021) - Cirillo, D.; Di Palma, M.; La Villetta, M.; Macaluso, A.; Mauro, A.; Vanoli, L.
Highlights: A numerical model is developed to predict the behaviour of a real micro-cogeneration system. The model includes a downdraft gasifier coupled with an internal combustion engine. The model takes into account gasification, cleaning, combustion and heat recovery. The numerical model has been validated with the experimental data acquired on site. The experimental data have been associated to their measurement uncertainties. Abstract: This work presents a numerical model developed to predict the behaviour of a real micro-cogeneration biomass gasification system, based on a fixed-bed downdraft gasifier, coupled with a spark-ignition internal combustion engine. The model developed by the authors takes into account all the thermo-physical processes occurring in the whole system: gasification, cleaning, combustion and heat recovery. The numerical model is based on the Gibbs free energy minimization, applying the restricted equilibrium method. The model has been validated with the experimental data collected during an extensive experimental campaign, and a good agreement between measured data and predicted results is obtained. The present validated model has proved to be a useful tool for analyzing the performance of real micro-CHP plants. The global electrical and thermal efficiencies predicted by the model are 19.9% and 17.8%, while the measured values are 19.5% and 21.7%, respectively. Some parametric analyses have been carried out in order to assess the performance of the system as a function of the main gasifier and engine parameters, and to predict the behaviour of the system.